2012
DOI: 10.3892/ol.2012.588
|View full text |Cite
|
Sign up to set email alerts
|

HPV-16/18 detection does not affect the prognosis of head and neck squamous cell carcinoma in younger and older patients

Abstract: Abstract.Recently, high-risk human papillomavirus (HPV) has emerged as a possible agent associated with head and neck squamous cell carcinoma (HNSCC) in younger patients. Therefore, the purpose of the present study was to assess the effect of age on the distribution of HPV-16/18 in HNSCC, together with the impact of the virus on patient prognosis. A longitudinal prospective study was used adjusted for age, gender, TNM staging, smoking status and alcohol consumption. HPV was detected by PCR with consensus prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
3
8
0
Order By: Relevance
“…In the present study, the most common tumor site was tongue, and there was no meaningful statistical relation between tumor location and the HPV status. Similar findings have been reported in other studies ( 19 , 29 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, the most common tumor site was tongue, and there was no meaningful statistical relation between tumor location and the HPV status. Similar findings have been reported in other studies ( 19 , 29 ).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, 53.3% of HPV-positive patients were males and 46.7% were females, and there was no meaningful relation between gender and the HPV status. Such findings have been observed in some other studies ( 29 ), although some studies on oropharynx lesions have reported that the HPV-positive cases are predominantly male ( 33 , 41 , 42 , 44 ). In the present study, the most common tumor site was tongue, and there was no meaningful statistical relation between tumor location and the HPV status.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Despite progress in research and therapy, patient survival has not significantly improved in recent years, posing a significant challenge for science ( Fraga et al, 2012 ; Oliveira et al, 2014 ) from 15 to 61 % of HNSCC arising derived from leukoplakia ( Domingos et al, 2017 ). Although retrospective cohort studies have shown that younger individuals are also at risk for the development of this neoplasm, HNSCC usually develops in middle-aged and older individuals ( Farias et al, 2010 ; Marques-Silva et al, 2012 ; Bewley and Farwell, 2017 ). HNSCC is a preventable disease, in which smoking and alcohol, considered the main risk factors, is associated with 90 % of the cases ( De Paula et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%